2020
DOI: 10.4012/dmj.2019-255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of apigenin on surface-associated characteristics and adherence of <i>Streptococcus mutans </i>

Abstract: Apigenin is a type of flavonols that exhibits anti-caries properties. Bacterial adherence is the initial step in the forming of a stable biofilm that leads to caries. Bacterial adherence is affected by surface characteristics, including hydrophobicity and bacterial aggregation. However, the effect of apigenin on surface characteristics of cariogenic bacteria has not been reported. We aimed to examine the effects of apigenin on adherence and biofilm formation of Streptococcus mutans UA159. Hydrophobicity and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Apigenin, also present in L. javanica, could be implicated in the antibioflm activity observed. Tis can be supported by the fndings of Liu et al [68], where apigenin was shown to reduce the initial adherence and bioflms formed by Streptococcus mutans.…”
Section: Discussionmentioning
confidence: 88%
“…Apigenin, also present in L. javanica, could be implicated in the antibioflm activity observed. Tis can be supported by the fndings of Liu et al [68], where apigenin was shown to reduce the initial adherence and bioflms formed by Streptococcus mutans.…”
Section: Discussionmentioning
confidence: 88%
“…[22][23][24]30 The karyogenic potential of Streptococcus mutans is attributed to its ability to form biofilms on tooth surfaces. 10,11,28,[33][34][35] The prevalence of dental caries in the population in developing countries is currently still high, so research is needed related to efforts to prevent dental caries. Currently, the therapy used in the prevention of dental caries is to use fluoride both systemically and topically.…”
Section: Discussionmentioning
confidence: 99%
“…Processes of bacterial colonization on tooth surfaces, known as biofilm formation, begin with the process of bacterial adherence. 10,16,28,34 The adherence of Streptococcus mutans bacteria works through the enzyme glucosyltransferase, which converts sucrose into glucan. 1,12,15,28 These glucans play a role in bacterial adherence, which will then form biofilms, which can increase the adherence of Streptococcus mutans to the tooth surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apigenin ( 1 ) and luteolin ( 2 ) are effective bactericides, respectively, against Streptococcus mutans and S. aureus by suppressing the adherence and biofilm formation through remodeling of their surface features. , Moreover, luteolin ( 2 ) injures the cell membrane integrity of biofilm bacteria since it breaks membrane cells and cell morphology . Acteoside ( 27 ) also can kill S. aureus through target serine/threonine phosphatase Stp1 …”
Section: Biological Activities and Molecular Pharmacologymentioning
confidence: 99%